2023
DOI: 10.1002/smll.202300109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Functional Group Modifications on the Photocatalytic Performance of g‐C3N4

Abstract: In recent years, photocatalysis has received increasing attention in alleviating energy scarcity and environmental treatment, and graphite carbon nitride (g‐C3N4) is used as an ideal photocatalyst. However, it still remains numerous challenges to obtain the desirable photocatalytic performance of intrinsic g‐C3N4. Functional group functionalization, formed by introducing functional groups into the bulk structure, is one of the common modification techniques to modulate the carrier dynamics and increases the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 156 publications
(201 reference statements)
0
28
0
Order By: Relevance
“…g-C 3 N 4 is a promising star in photocatalytic hydrogen evolution owing to its low cost, broad light absorption range, and excellent stability. The sp 2 -hybridized C and N atoms in g-C 3 N 4 provide a π-conjugated electronic structure, which makes g-C 3 N 4 an ideal candidate for analysis the function of π–π interaction in photocatalysis. We synthesized the g-C 3 N 4 by directly heating urea in a muffle furnace.…”
Section: Results and Discussionmentioning
confidence: 99%
“…g-C 3 N 4 is a promising star in photocatalytic hydrogen evolution owing to its low cost, broad light absorption range, and excellent stability. The sp 2 -hybridized C and N atoms in g-C 3 N 4 provide a π-conjugated electronic structure, which makes g-C 3 N 4 an ideal candidate for analysis the function of π–π interaction in photocatalysis. We synthesized the g-C 3 N 4 by directly heating urea in a muffle furnace.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The widely investigated grafting groups include aromatic motifs, carbon nitride allotropes, and C-chains. 66–68 Xu et al 69 constructed a D-A system by incorporating thiophene-2,5-dicarbaldehyde (TDA) into the g-C 3 N 4 network, and found that the modified g-C 3 N 4 displayed an obviously improved photocatalytic performance for bisphenol A degradation and H 2 evolution from water-splitting. The experimental and calculation results (Fig.…”
Section: Structural Modulation Of G-c3n4mentioning
confidence: 99%
“…However, the intermittent and unpredictable nature of solar energy makes it difficult to use and store on site. In order to achieve sustainable development, photocatalysis technology can convert solar energy into a green and clean energy source, hydrogen, that can be stored, transported, and used. In order to achieve this goal, the key is to develop semiconductor photocatalysts with a wide light absorption range, efficient charge separation and transfer, and efficient surface catalytic behavior to improve photogenerated charge separation efficiency and photocatalytic performance. …”
Section: Introductionmentioning
confidence: 99%